2003
DOI: 10.1021/bi034627g
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Acting Hepatitis Delta Virus Ribozyme:  Catalytic Core and Global Structure Are Dependent on the 5‘ Substrate Sequence

Abstract: The hepatitis delta virus (HDV), an infectious human pathogen affecting millions of people worldwide, leads to intensified disease symptoms, including progression to liver cirrhosis upon coinfection with its helper virus, HBV. Both the circular RNA genome of HDV and its complementary antigenome contain a common cis-cleaving catalytic RNA motif, the HDV ribozyme, which plays a crucial role in viral replication. Previously, the crystal structure of the product form of the cis-acting genomic HDV ribozyme has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
77
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(94 citation statements)
references
References 45 publications
17
77
0
Order By: Relevance
“…126 In the HDV and CPEB3 ribozymes, the upstream sequences have been shown to markedly decrease self-cleavage activity if they are capable of extending the P1 helix by base pairing with nucleotides required to form the P1.1 helix, thereby disrupting active-site formation of the molecule. 55,56,59,98 An identical event is observed among the R2 ribozymes. As the number of alternate base pairs that the upstream sequence can form is increased from zero to three, the rate constants decrease from approximately 80 to 0.30 per hour, respectively.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…126 In the HDV and CPEB3 ribozymes, the upstream sequences have been shown to markedly decrease self-cleavage activity if they are capable of extending the P1 helix by base pairing with nucleotides required to form the P1.1 helix, thereby disrupting active-site formation of the molecule. 55,56,59,98 An identical event is observed among the R2 ribozymes. As the number of alternate base pairs that the upstream sequence can form is increased from zero to three, the rate constants decrease from approximately 80 to 0.30 per hour, respectively.…”
mentioning
confidence: 70%
“…Such kinetically trapped alternative conformations can form through improper base-pairing interactions of flanking sequences with the ribozyme core or even within the cores. 50,[55][56][57][58][59][60][61] Alternative conformations result in slow overall cleavage rates, biphasic kinetics, or high fractions of uncleaved ribozymes. Mutations that destabilize these ribozyme-disrupting interactions tend to result in faster cleaving ribozymes.…”
Section: Ribozyme Foldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, in vitro transcribed, gel-purified mRNA was refolded in the same S30 buffer where we observed bypassing, and probed with either 1 mM Tb 3+ ions as described (Walter et al 2000;Walter 2003, 2005;Jeong et al 2003;Harris et al 2004;Sefcikova et al 2007a,b) or 2 mM of the SHAPE reagent 1M7 (Mortimer and Weeks 2007;Gherghe et al 2008Gherghe et al , 2010Watts et al 2009). These two complementary reagents target accessible 2 ′ -OH groups, either to deprotonate them and cleave the adjacent phosphodiester bond (Tb 3+ ) or to acylate them (1M7).…”
Section: Conditions For Translation and Bypassing Of Gene 60 Mrna In mentioning
confidence: 99%
“…Although most ribozyme studies have revealed single turnover behavior [14,16,17], sometimes the data are better fit by bi-exponential kinetics [18].…”
Section: Ribozyme: Single Turnover Methodsmentioning
confidence: 99%